KEMATIAN IBU: SUATU TINJAUAN SOSIAL-BUDAYA - Budi Rajab (Jurnal Masyarakat dan Budaya, 2009)
Mother mortality rate in Indonesia remains considerably high. The cause of maternal mortality indirectly is much related with the problems of poverty, the independent role of women in decision making within the family, and the public health services, which continues to be a centralistic-bureaucracy. In Costa Rica, Srilanka, and Kerala province in India, even though the majority of their citizens are poor as in Indonesia the maternal mortality is falling significantly. The reason that make this possible is because a strategy and a program of women empowerment in making independent decisions have been developed together with a model of participative public health services, which is cooperatively carried out by government and local community institutions dealing with community health problems that are affordable and comprehend for the economy and education of the community. The society and government of Indonesia may get a lesson by learning from the strategy and health programs from those three countries. Keywords: Maternal Mortality, Poverty, Women Dependency, Maternal Heath Service